2005
DOI: 10.1007/s11258-005-9073-4
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and root extracts of the invasive shrub, Lonicera maackii, inhibit seed germination of three herbs with no autotoxic effects

Abstract: In addition to effects mediated by resource competition, some invasive plants may impact surrounding vegetation by secreting compounds that are directly inhibitory to growth. Lonicera maackii, an invasive Asian shrub of forests and open areas in eastern and midwestern North America, has devastating effects on understory vegetation, some of which persist even after this shrub is removed. In this study, we explored the potential of aqueous extracts of the leaves and roots of this plant to inhibit seed germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 26 publications
8
129
2
Order By: Relevance
“…Naderi and Bijanzadeh (2012) identified the potential of allelopathic effects of leaf, stem and root extracts of ten Iranian rice cultivars on barnyard grass, which leaf extract exhibited the strongest growth inhibitory activity followed by root and stem extracts. Numerous researchers also reported that each plant part showed significant difference effects on the growth of test plant species (Dorning and Cipollini, 2006;Fateh et al, 2012;Grisi et al, 2012;Pirzad et al, 2012;Liu et al, 2003;Tabrizi and Yarnia, 2011). It has also been reported that the compounds in roots reach more easily to the surrounding plant roots than the compounds in leaves (Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Naderi and Bijanzadeh (2012) identified the potential of allelopathic effects of leaf, stem and root extracts of ten Iranian rice cultivars on barnyard grass, which leaf extract exhibited the strongest growth inhibitory activity followed by root and stem extracts. Numerous researchers also reported that each plant part showed significant difference effects on the growth of test plant species (Dorning and Cipollini, 2006;Fateh et al, 2012;Grisi et al, 2012;Pirzad et al, 2012;Liu et al, 2003;Tabrizi and Yarnia, 2011). It has also been reported that the compounds in roots reach more easily to the surrounding plant roots than the compounds in leaves (Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Allelopathic potential is an important attribute to the success of an invasive species in natural ecosystems, particularly when the species produces novel biochemical weapons (Callaway & Ridenour 2004). Interactions associated with allelochemicals produced by invasive or native plant species have the potential to impact seed germination, seedling growth, development, and establishment of neighboring plant species, as well as of the same species, in both natural and agricultural systems (Dorning & Cipollini 2006;Lara-Nu´n˜ez et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may allow honeysuckle seeds to escape predation while also reducing competition from native shade-tolerant tree species. Extracts produced from the leaves and root of Lonicera maackii have been shown to decrease the germination of orange jewelweed (Impatiens capensis), garlic mustard (Alliaria petiolata), and thale cress (Arabidopsis thaliana) in the laboratory (Dorning and Cipollini 2006). Similarly, Cipollini et al (2008a) reported thale cress to display reduced growth, decreased reproduction, and a constrained ability to responsed to higher nutrient availability after honeysuckle extracts were applied to soils.…”
Section: Plantsmentioning
confidence: 99%